Harveya kiangombensis (Orobanchaceae), a new parasitic species from Kenya, East Africa - Ngugi, Grace; Kirika, Paul M.; Mwachala, Geoffrey (Phytotaxa, 2022)
A new holoparasitic species of Orobanchaceae, Harveya kiangombensis, is here described and illustrated. This species is easily distinguished from the closely related H. liebuschiana by its glandular pubescent pedicels, the position of its flowers that occur singly in the leaf axils, and its acute calyx lobes. An assessment of the conservation status of the new species is provided.